S1 pocket fingerprints of human and bacterial methionine aminopeptidases determined using fluorogenic libraries of substrates and phosphorus based inhibitors - Poręba, Marcin; Marschner, Aline; Klein, Christian D. (Biochimie, 2012)
Methionyl aminopeptidases (MetAPs) are metallo-dependent proteases responsible for removing of N-terminal methionine residue of peptides and proteins during protein maturation and activation. In this report we use a comprehensive strategy to screen the substrate specificity of three methionyl aminopeptidases: Homo sapiens MetAP-1, Homo sapiens MetAP-2 and Escherichia coli MetAP-1. By utilizing a 65-membered fluorogenic substrate library consisting of natural and unnatural amino acids we established detailed substrate preferences of each enzyme in the S1 pocket. Our results show that this pocket is highly conserved for all investigated MetAPs, very stringent for methionine, and that several unnatural amino acids with methionine-like characteristics were also well hydrolyzed by MetAPs. The substrate-derived results were verified using several phosphonate and phosphinate-based inhibitors.